Religion and Modern Society: Criticism of Phil Zuckerman's Ideas on Religion - Alfathoni, Waldi; Wijaya, Wijaya; Nugroho, Nugroho (Universitas Islam Negeri Imam Bonjol Padang, 2024)
Phil Zuckerman, a prominent sociologist and professor at Pitzer College, California, explores the landscape of secularism in Denmark and Sweden through his empirical research. His work, particularly highlighted in